Clinical and Nutritional Assessment of Short Statured Indian Children with Celiac Disease - Mali, Lalit P; Meena, Shyam Sundar; Khatri, Poonam Chand; Kumar, T V Ram; Kumar, Praveen (Journal of Nepal Paediatric Society, 2013)
Introduction: Celiac disease is an autoimmune disease, which is increasingly recognized as a cause of short stature in genetically susceptible population. The present study was undertaken to look for prevalence of celiac disease among the pediatric population with short stature (SS) and to study characteristics of these short statured children with celiac disease. Materials and Methods: This is a prospective study conducted at a tertiary teaching hospital at Bikaner, Rajasthan to look for the occurrence of celiac disease amongst the pediatric population (<15 years) with short stature (n=100). Other common causes of short stature were also identified. Results: Out of 100 short statured children, 38 (38%) had celiac disease and other major causes responsible were hypothyroidism, pituitary disorders, constitutional growth delay, and familial short stature. Chronic diarrhea, anorexia, anemia and behavioral changes were statistically more common in short statured children (<15 years) having celiac disease than non celiac patients. Conclusion: We conclude that celiac disease is not an uncommon cause of short stature and stunted growth in this region. All short statured patients should be screened for celiac disease. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7912 J Nepal Paediatr Soc. 2013; 33(2):91-94